Análise da competitividade de um aglomerado produtivo pelo viés do empreendedorismo: uma proposta metodológica - Moraes, Simone Cristina Silva (2008)
The objective of this work was to develop a methodology to analyze thecompetitiveness of Productive Clusters by the bias of entrepreneurship, searching on the Metal Furniture and Storage System and Logistics industries in Ponta Grossa, Paraná State, in Brazil. In this aspect, the enterprising profile of each company was analyzed in the vision of the leaders and collaborators in the production area. Under the prism of the leaders, the following items were analyzed: the degree of innovation, multilateral cooperation, market strategy, standardization, interaction with customers and suppliers, internal communication, workforce, leadership and organizational resilience. And from the employees’ perspective, especially those from the productive sector, were examined the motivation, the internal communication, the creativity, the quality of life at work, the relationship with leaders and organizational resilience. For methodological procedures, the survey is classified as inductive, applied and quantitative. The method of procedure was the survey. Data collection was performed in loco, with 15 owners or member-managers, as well as 251 employees from the productive sector distributed proportionately in 15 companies. During the data collection one questionnaire and application form containing were used structured questions, creating a model to analyze the entrepreneur within company management in the productive clusters. The main results showed that the productive cluster is characterized with a moderate entrepreneur profile, despite of all the attributes of competitiveness examined needed for strategies that involve more aggressive, durable, competitive and sustainable structuring actions. It was noticed that the holistic and systemic vision is missing, among other factors, by the business leaders, so that those strategies could be implemented.